Pengembangan Bahan Ajar Interaktif Menggunakan Aplikasi Articulate Storyline Berbasis Pendekatan PMRI pada Materi Bangun Datar di Kelas IV Sekolah Dasar - Mahirah Naifah Mardhiah; Melva Zainil (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to develop interactive teaching materials using the Articulate Storyline 3 application based on the Indonesian Realistic Mathematics Education Approach (PMRI) on the material of plane figures for grade IV of Elementary School that is valid, practical, and effective. The study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of grade IV students at SDN 14 Koto Lalang, SDN 12 Padang Besi, and SDN 10 Bandar Buat. Data collection techniques used expert validation sheets, teacher and student practicality questionnaires, and learning outcome tests. The results showed that the developed teaching materials obtained a validity level of 94.25% with a valid category. The practicality results showed a very practical category with a percentage of teacher and student responses above 87%. The effectiveness of the teaching materials is seen from the increase in student learning outcomes with the percentage of learning completion reaching 80% at SDN 14 Koto Lalang, 81% at SDN 12 Padang Besi, and 82.61% at SDN 10 Bandar Buat. Thus, PMRI-based interactive teaching materials using Articulate Storyline 3 are suitable for use in learning mathematics on flat shapes in grade IV of Elementary School.